Beeng Köödh Mi Teeni Paar Wun Ócag Ka Jaag Yi Wun Kidï Wänyi Cingi Tyëngpur (Men-A Álor). Cagi Beeng Köödh Mi Teeni Pac: Wänyithinh 1 Kì Ri 3 - Vernooy, Ronnie; Bessette, Guy; Sthapit, Bhuwon; Dibiloane, Angeline kí; Lettie Maluleke, Nkat; Abner Matelele, Lehlogonolo; Mokoena, Mpolokeng; Phora, George; Sema, Precious; Thabo, Tjikana (2023)
This farmer’s handbook is a companion (https://hdl.handle.net/10568/81286). The three booklets making up this farmer’s handbook were written and designed for rural producers who are interested in establishing, supporting, and managing a community seed bank. Each booklet focuses on a theme presented by the members of a community seed bank in Africa, Asia, and Latin America. Booklet 1 is available at: [ https://hdl.handle.net/10568/151619 ] and booklet 3 is available at [ https://hdl.handle.net/10568/151622 ].